Effect of resin composites with sodium trimetaphosphate with or without fluoride on hardness, ion release and enamel demineralization - Ferreira Tiveron, Adelisa Rodolfo [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Gaban, Gabriel [UNESP]; Sassaki, Kikue Takebayasbi [UNESP]; Pedrini, Denise [UNESP] (Mosher & Linder, Inc, 2013)
Purpose: To evaluate the effect of the addition of sodium trimetaphosphate (TMP) with or without fluoride on enamel demineralization, and the hardness and release of fluoride and TMP of resin composites. Methods: Bovine enamel slabs (4x3x3 mm) were prepared and selected based on initial surface hardness (n= 96). Eight experimental resin composites were formulated, according to the combination of TMP and sodium fluoride (NaF): TMP/NaF-free (control), 1.6% sodium fluoride (NaF), and 1.5%, 14.1% and 36.8% TMP with and without 1.6% NaF. Resin composite specimens (n= 24) were attached to the enamel slabs with wax and the sets were subjected to pH cycling. Next, surface and cross-sectional hardness and fluoride content of enamel as well as fluoride and TNT release and hardness of the materials were evaluated. Data were statistically analyzed using ANOVA (P< 0.05). Results: The presence of fluoride in enamel was similar in fluoridated resin composites (P> 0.05), but higher than in the other materials (P< 0.05). The combination of 14.1% TMP and fluoride resulted in less demineralization, especially on lesion surface (P< 0.05). The presence of TMP increased fluoride release from the materials and reduced their hardness.